The Arteriovenous Connection in the Spermatic Cord in the Variable Squirrel (Callosciurus finlaysoni) - Worawut Rerkamnuaychoke; Narong Chungsamarnyart; Apinun Suprasert; Boontham Chongcharoen (Agriculture and Natural Resources, 1993)
In the variable squirrel (Callosciurus finlaysoni), four to five ramifying arterioles arose directly from the testicular artery and then gave off numerous small capillaries. The capillaries made a series of anastomoses with neighbouring counterpart capillaries to become a complicated network. Some of the capillaries drained into a small venule, which were connected directly with the testicular vein (pampiniform plexus), to form an arteriovenous connection (A-V shunt) between the testicular artery and the pampiniform plexus. This A-V shunt appeared to make the transfer of substances from the pampiniform plexus to the testicular artery more efficient. The shunt might control the volume of the blood draining into the testis. In addition, the capillaries were covered by vesiculated cells which were located adjacent to the pericytes of the capillaries. The vesiculated cells contained abundant mitochondria, rough endoplasmic reticulum, Golgi complex and cytoplasmic vesicles. The vesiculated cells could provide support for the capillaries and prevented their collapse when the shunts were closed.